Comparison Between Body Mass Index and Side Effect Incidence in Bladder Cancer Patients Treated with Gemcitabine-Cisplatin at Dr. Saiful Anwar General Hospital Malang, Indonesia - Seputra, Kurnia Penta; Ardiani, Astarin; Daryanto, Besut (International Journal of Psychosocial Rehabilitation, 2020)
Gemcitabine-Cisplatin chemotherapy is one of bladder cancer treatment available in Dr. Saiful Anwar General Hospital Malang, although chemotherapy are beneficent, it also gave many unwanted side effect. Body Mass Index (BMI) said to have roles in cancer development and therapy outcome. This study aimed to compare BMI with side effect incidence in bladder cancer patients receiving six course of Gemcitabine- Cisplatin chemotherapy. Eighteen bladder cancer patients receiving Gemcitabine-Cisplatin chemotherapy by urology oncologist from 2016 to 2018 were recorded. The patients were followed during their six series of chemotherapy and any possible side effect were recorded. The data then analysed with chi square and T-test using SPSS programme. Body mass index (BMI) including normal weight, underweight, overweight and obese, account to 73.3%; 6.67%; 13.3%; and 6.67% respectively . Pathology finding consist of Transitional Cell Carcinoma high grade (46.7%) and low grade (53.3%). All 15 patients underwent six series of Gemcitabine-Cisplatin chemotherapy, side effects occurred during the whole series including, nausea(80%), fatigue(87%), vomiting(27%), alopecia(13.3%), infection(20%). Hematologic side effect including anemia, leucopenia, thrombocytopenia and nephrotoxicity Hematologic side effects such as: anemia, leucopenia and thrombocytopenia and also nephrotoxicity occurred in all 15 patients, minimally once of the six series of chemotherapy. When those side effect compared with BMI there were no statistical significant between the them with (p = 0.360), (p = 0.310), (p = 0.634), and (p = 0.423) respectively. Body Mass Index has no relation with side effect occurrence in bladder cancer patients receiving Gemcitabine-Cisplatin chemotherapy.